Enhanced hydrogen evolution efficiency achieved by atomically controlled platinum deposited on gold nanodendrites with high-index surfaces. Issue 40 (5th October 2021) - Lai, Ying-Huang; Li, Sin-Ren; M. G, Swathi; Chang, Hsiao-Tzu; Huang, Yu-Bin; Li, Yen-Ken; Chen, Yu-Mei; Patil, Shivaraj B.; Chang, Shu-Yi; Chen, Po-Kai; Chang, Chia-Che; Chen, Yi-Chia; et al.
Abstract : Minimum Pt atom deposition on the Au NDs surface (O-Pt on Au NDs) by the constant-current deposition method in acidic conditions played a substantial role in accomplishing the Tafel reaction in the hydrogen evolution reaction. Abstract : There have been several studies on the catalytic activity of the hydrogen evolution reaction (HER) using ultralow loading of Pt catalysts or even Pt single atom catalysts. However, Pt single atom deposited on the surface of the carbon or metal oxide material has some drawbacks, such as high possibility of Pt desorption from the supported material in the electrolyte. Besides, from the reaction mechanism perspective, each Pt atom in this type of catalyst is too far to achieve high HER efficiency via the Tafel reaction pathway. In this work, gold nanodendrites (Au NDs) with high facet surface were chosen as the supported materials for studying the relation between the low loading amount of Pt atoms and the reaction mechanism of the HER activity. The atomic deposition of Pt atoms on the surface of Au NDs can be controlled effectively using a constant-current synthetic method. It was found that the HER electrocatalytic activity of ultralow Pt loading catalyst, with Pt atoms to total surface atoms of Au NDs (O-Pt on Au NDs) of 5.5%, could achieve high efficiency via the Tafel reaction pathway, showing a low overpotential of ∼18 mV at a current density of 10 mA cm −2 and a small Tafel slope of ∼31 mV dec −1, which is close to that of commercial Pt/C with 20 wt% Pt. As confirmed by Inductively Coupled Plasma Mass Spectrometry(ICP-MS), the Pt loading amount of O-Pt on Au NDs was ∼3.8 ± 0.2 μg cm −2 on a physical area of carbon fiber paper. The turnover frequency (TOF) of O-Pt on Au NDs was found to be 40.1 ± 2.5 H2 per s at 50 mV. This work provides a feasible approach to control the atomic deposition of Pt on a specific substrate as an active catalyst for various catalytic applications.